+0  
 
+1
41
2
avatar+62 

When the expression $-5x^2+20x-17$ is written in the form $a(x+d)^2+e$, where $a$, $d$, and $e$ are constants, then what is the sum $a+d+e$?

 

 

thanks so much!

AnonymousConfusedGuy  Oct 22, 2017
Sort: 

2+0 Answers

 #1
avatar+62 
+1

Please could someone respond?

AnonymousConfusedGuy  Oct 22, 2017
 #2
avatar+78577 
+2

 

-5x^2+20x-17    divide through by - 5

 

-5 ( x^2 - 4x + 17/5)

 

Take 1/2 of 4  =  2.......square it = 4.....add it and subtract it

 

-5 ( x^2 - 4x + 4 + 17/5 - 4)

 

Factor the first three terms and simplify

 

-5 [ (x -2)^2  +  17/5 - 20/5 ] 

 

-5 [ (x - 2)^2  - 3/5]

 

-5( x - 2)^2  + 3

 

a = -5   d = -2    and  e = 3

 

So

 

a + d + e  =   -5 + (-2) + 3  =   -7 + 3  =  - 4 

 

 

cool cool cool

CPhill  Oct 22, 2017

16 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details